2021
DOI: 10.3390/molecules26185604
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of Pyrazolo[4′,3′:5,6]pyrano[4,3-c][1,2]oxazoles via Intramolecular Nitrile Oxide Cycloaddition

Abstract: A simple and efficient synthetic route to the novel 3a,4-dihydro-3H,7H- and 4H,7H-pyrazolo[4′,3′:5,6]pyrano[4,3-c][1,2]oxazole ring systems from 3-(prop-2-en-1-yloxy)- or 3-(prop-2-yn-1-yloxy)-1H-pyrazole-4-carbaldehyde oximes has been developed by employing the intramolecular nitrile oxide cycloaddition (INOC) reaction as the key step. The configuration of intermediate aldoximes was unambiguously determined using NOESY experimental data and comparison of the magnitudes of 1JCH coupling constants of the iminyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
(122 reference statements)
1
6
0
Order By: Relevance
“…As expected, the 1 H, 13 C and 15 N NMR chemical shifts and the relevant correlations in the two-dimensional NMR spectra of these two isomeric 1,2-oxazoles were highly similar. The unambiguous formation of 1,2-oxazole (isoxazole) moiety was easily deduced from 1 H-15 N HMBC spectral data, as it clearly showed a distinct longrange correlation between the isoxazole methine 4′-H proton and nitrogen N-2′, which resonated at δ −18.6 and −19.6 ppm for compounds 15 and 14, respectively, and this is in good agreement with the data reported in the literature [69]. The 2 Hz optimized 1 H- 15 N HMBC spectra hinted in favor of these structures.…”
Section: Resultssupporting
confidence: 88%
“…As expected, the 1 H, 13 C and 15 N NMR chemical shifts and the relevant correlations in the two-dimensional NMR spectra of these two isomeric 1,2-oxazoles were highly similar. The unambiguous formation of 1,2-oxazole (isoxazole) moiety was easily deduced from 1 H-15 N HMBC spectral data, as it clearly showed a distinct longrange correlation between the isoxazole methine 4′-H proton and nitrogen N-2′, which resonated at δ −18.6 and −19.6 ppm for compounds 15 and 14, respectively, and this is in good agreement with the data reported in the literature [69]. The 2 Hz optimized 1 H- 15 N HMBC spectra hinted in favor of these structures.…”
Section: Resultssupporting
confidence: 88%
“…Pyrazolo [4 ,3 :5,6]pyrano [4,3-c] [1,2]oxazoles with various substituents at C-3 or C-7 were synthetized. Through extensive NMR spectroscopic studies carried out using standard and advanced methods, the authors unambiguously confirmed the predomination of the syn-isomer of intermediate aldoximes [9]. Bearing in mind the remarkable biological activities of both pyrazole and thiazole scaffolds, Y. N. Mabkhot and coworkers developed a convenient synthesis of novel pyrazolo [5,1-b]thiazole-based heterocycles.…”
mentioning
confidence: 88%
“…[29][30][31] Replacement of the central pyrrole to pyrazole is expected to change e.g., the energy of the highest occupied molecular orbital (HOMO) which is associated with increased metabolic stability. 32 In continuation of our previous works devoted to synthesis and investigation of pyrazole derivatives, [33][34][35][36][37][38][39][40][41] in this study we ought to synthesize and investigate various functionalized pyrazole derivatives of lamellarin O. The goal was based on the scaffold hopping of the pyrrole ring in natural lamellarin O to its pyrazole counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our previous works devoted to synthesis and investigation of pyrazole derivatives, 33–41 in this study we ought to synthesize and investigate various functionalized pyrazole derivatives of lamellarin O. The goal was based on the scaffold hopping of the pyrrole ring in natural lamellarin O to its pyrazole counterpart.…”
Section: Introductionmentioning
confidence: 99%